2021
DOI: 10.1007/s12028-021-01331-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Milrinone for Cerebral Vasospasm in Subarachnoid Hemorrhage: The MILRISPASM Controlled Before–After Study

Abstract: Background: Intravenous (IV) milrinone, in combination with induced hypertension, has been proposed as a treatment option for cerebral vasospasm after aneurysmal subarachnoid hemorrhage (aSAH). However, data on its safety and efficacy are scarce. Methods:This was a controlled observational study conducted in an academic hospital with prospectively and retrospectively collected data. Consecutive patients with cerebral vasospasm following aSAH and treated with both IV milrinone (0.5 µg/kg/min −1 , as part of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…It reduces the amount of calcium available for the contraction of vascular smooth muscle cells. The increase of second messengers in cell functions may bring along a broad range of side effects (21)(22)(23). In our retrospective analysis, 1 mg milrinone provoked a self-limiting cardiac arrhythmia in one patient, similar to the case report of Vimala et al (23).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It reduces the amount of calcium available for the contraction of vascular smooth muscle cells. The increase of second messengers in cell functions may bring along a broad range of side effects (21)(22)(23). In our retrospective analysis, 1 mg milrinone provoked a self-limiting cardiac arrhythmia in one patient, similar to the case report of Vimala et al (23).…”
Section: Discussionsupporting
confidence: 83%
“…In our retrospective analysis, 1 mg milrinone provoked a self-limiting cardiac arrhythmia in one patient, similar to the case report of Vimala et al ( 23 ). In former studies, polyuria, hypokalemia, and hyponatremia were expected adverse effects ( 5 , 22 ). Myocardial ischemia and thrombocytopenia were infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…Milrinone, possessing a mechanism of action for the reversal of cerebral vasospasm as well as potentially antiinflammatory effects, has been identified as a promising therapeutic agent for DCI [22]. Several recent preliminary studies showed a potential benefit of milrinone for the management of DCI-related vasospasm and encourage the conduction of confirmatory randomized trials [23][24][25]. Awaiting more data from well-powered studies, we are unable to provide any recommendation regarding the utilization of milrinone in case of DCI related to refractory vasospasm.…”
Section: Dci-related Vasospasm Managementmentioning
confidence: 99%
“…These authors did not see a substantial difference in outcome between the two strategies. In contrast, Lakhal et al reported from their monocentric historical comparison significantly lower rates of brain infarction and poor clinical outcome using intravenous milrinone in combination with induced hypertension, compared to induced hypertension alone [ 14 ].…”
Section: Discussionmentioning
confidence: 99%